Dampak Pinjaman Mikro terhadap Kesejahteraan Rumah Tangga Perempuan Pengusaha Mikro dan Kecil - Sjari M, Dewi Ratna; Sinaga, Bonar M.; Kusnadi, Nunung; Syaukat, Yusman (UI Scholars Hub, 2022)
This study aims to examine how credit lending can improve MSEs performance, its impact on women micro and small entrepreneurs (PPMK) household welfare, and the determinants of their disinterest in subsidised loans. Using a sample of 82 PPMK households in Depok City and Bogor Regency with the Propensity Score Matching (PSM) method, the results showed loans could boost business income. Still, the government’s credit with low-interest rates is not the primary choice due to limited knowledge, an obligation for collateral, and religious issues such as usury. This study also shows government credit assistance can improve the welfare of MSE households.